Viet Nam vocational training report 2011 - (:unkn) unknown (My University, 2012)
This is the first comprehensive report on vocational training in Vietnam published by the National Institute for Vocational Training (NIVT) in cooperation with the Federal Institute for Vocational Education and Training (BIBB) and Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ). "The report is developed with the primary goal of providing information and evidence on vocational training to policy-makers, managers; vocational institutions, manpower training and development institutions, enterprises and laborers of Vietnam; international organizations with interest in vocational training in Vietnam. [It] map[s] out the overall 'picture' of vocational training in Vietnam at present stage (updated as of December 2011); strengths, weaknesses and policy limitations on vocational training system, whereby to make recommendation for finalization of policy documents in the interest of enhancing effectiveness and efficiency of vocational training. However, due to time constraints, Vietnam Vocational Training Report 2011 is developed mainly on the basis of analysis of data published by competent authorities, such as General Statistics Office (GSO), Ministry of Labor, Invalids and Social Affairs (MOLISA)/General Department of Vocational Training (GDVT)." (Text extract, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.3.4 Asien; Berufsbildungsbericht; Berufsbildungssystem; Berufsbildungspolitik; Monitoring; Vietnam